Mission, A Cultural Confrontation: Swami Vivekananda and The American Missionary Movement - Brown, Linda Keller (Journal of Dharma, 1999)
In 1893 there occurred a unique event in the history of, organized religion. Commemorating the four hundredth anniversary of the discovery of. America, the World-Columbian Exposition opened in Chicago to display the achievements of Western civilization. Since "faith in a Divine Power ... has been, like the sun, a life-giving and fructifying potency in man's ... development,"] one of the twenty congresses was devoted to religion. When the Parliament convened on September 11, 1893, among the Oriental delegates on the platform were: Proptop Chandra Mazoomdar of Calcutta and B.B. Nagarkar of Bombay, both representing the Brhamo Samaj; Dharmapala of the Ceylon Buddhists; Virchand Gandhi for the Jains; and Chakravarti and Annie Besant of the Theosophical Society. Seated with this illustrious group was a young Hindu, Swami Vivekananda, who "represented no particular sect, but the Universal Religion of the Vedas.